2018
DOI: 10.3390/geosciences8060204
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Morphology of Asymmetric Barchans in the Central Hexi Corridor of Northwest China

Abstract: Crescent-shaped barchan dunes often display an asymmetric shape, with one limb longer than the other. As shown in previous studies, asymmetric bimodal winds constitute one major cause of barchan asymmetry, but the heterogeneous conditions of sand availability or flux, as well as topographic influences, may be also important. Understanding the morphology and dynamics of asymmetric barchans may have an impact in a broad range of areas, particularly as these dunes may serve as a proxy for planetary wind regimes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 61 publications
(105 reference statements)
1
19
0
Order By: Relevance
“…The similar amounts of sand and dust mean that nebkhas can both capture these materials and serve as a source of dust emission. This phenomenon has been documented for oasis and sandy desert nebkhas in north-western China (Sweeney et al, 2016;Zou et al, 2016) and in Israel's Negev Desert, where nebkhas can trap about 80% of the transported sand (Kidron & Zohar, 2016).…”
Section: Nebkhas and Dust Emissionmentioning
confidence: 80%
See 1 more Smart Citation
“…The similar amounts of sand and dust mean that nebkhas can both capture these materials and serve as a source of dust emission. This phenomenon has been documented for oasis and sandy desert nebkhas in north-western China (Sweeney et al, 2016;Zou et al, 2016) and in Israel's Negev Desert, where nebkhas can trap about 80% of the transported sand (Kidron & Zohar, 2016).…”
Section: Nebkhas and Dust Emissionmentioning
confidence: 80%
“…Nebkhas, also called coppice or shrub-coppice dunes (Hesp & Smyth, 2017), form in any region where there is a strong wind regime, available aeolian sediment capable of being entrained by these winds, and vegetation that can trap the transported sediment. Because of the vast regions they occupy worldwide, their formation and development have been extensively studied (Hasi et al, 2013;Zhang et al, 2013;Gillies et al, 2014;Hesp & Smyth, 2017;Mayaud et al, 2017;Zuo et al, 2018), along with their morphological properties (Yang et al, 2015) and environmental implications (Wang et al, 2006(Wang et al, , 2010Zou et al, 2016;Yan et al, 2019). However, there has been little research on the nebkhas that develop in areas of gobi desert (where the surface is covered with closely packed, interlocking angular or rounded rock fragments of gravel and cobble size).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous results from both field observations and wind tunnel experiments, the threshold velocity in the study region is 6.0 m s À1 (Zu et al, 2008). Although this approach makes a number of interpretative simplifications and assumptions, previous studies of the wind energy environments of global sand seas have demonstrated its value (Zhang et al, 2018b). More detailed descriptions of the method can be found in previous studies (Fryberger and Dean, 1979;Zhang et al, 2015).…”
Section: Wind Regimesmentioning
confidence: 98%
“…The main methods of studying dune migration are monitoring of changes in dune morphology (Dong et al, 2000), comparison of remote-sensing images from different years (Al-Mutiry et al, 2016;Boulghobra and Dridi, 2016;Baughman et al, 2018;Hoover et al, 2018), numerical simulation (Tsoar, 1984;Durán et al, 2010;Parteli et al, 2014;Ping et al, 2016), using multi-temporal LiDAR data and a new approach named the 'pairs of source and target points' (Dong, 2015), and dating of sediments at different depths below the dune's slipface using optically stimulated luminescence dating. Highresolution satellite images have proven to be an ideal information source for obtaining the information about dune migration (Bourke, 2010;Hereher, 2010;Dakir et al, 2016;Zhang et al, 2018b). By comparing satellite images from different dates, we can obtain key information such as the migration rate, migration direction and changes of dune morphometric parameters.…”
Section: Definition Of Dune Migration Rate and Directionmentioning
confidence: 99%
See 1 more Smart Citation